PARAMETRIC ANALYSIS AND OPTIMIZATION OF AL-MG-SI/EGGSHELL PARTICULATE COMPOSITE MATERIAL USING RESPONSE SURFACE METHODOLOGY - Eze, Samuel Chikezie; Yawas, D.S; Dauda, E.T; Izelu, C.O (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2022)
In this study, Al-Mg-Si alloy obtained from scrap aluminum profile was reinforced with calcined eggshell particulates at varying particle sizes (25µm, 50 µm and 75 µm) and concentrations (1wt%, 2 wt% and 3 wt %) respectively. Data generated from series of experimental runs in which the effect of the factor inputs such as eggshell size and concentration had on the response variables (hardness, yield strength, modulus of elasticity, thermal conductivity, impact strength, density and corrosion rate) of the Al-Mg-Si/Eggshell particulate composite material were recorded The response surface methodology, based on central composite design of experiment, was used and the analysis performed in Design Expert 9 software environment. Regression models were obtained and evaluated for the response variables as functions of the selected factors. The optimal settings of these factors required to either maximize or minimize the response variables were also determined. The result showed that the optimum setting of the factors ‘A’ (ESP size) at 25 µm, and ‘B’ (ESP Conc.) at 1wt. %, would maximize H to a value of 34.876 BHN, YS to a value of 38.163 N/mm2, ME to a value of 23729.405 N/mm2 TC to 54.672 W/m.oC, and IE to 15.218 J while minimizing D to a value of 2623.058 Kg/m3 and CR to a value of 0.921 MPY respectively with desirability of 0.940332, 0.363653, 1.00, 0.516979, 0.519945, 0.37036 and 0.916263 which occurred within the selected design space.